2004
DOI: 10.1097/01.moh.0000137915.88478.23
|View full text |Cite
|
Sign up to set email alerts
|

Solvent/detergent-treated plasma: composition, efficacy, and safety

Abstract: Future research should seek to optimize the composition of solvent/detergent-treated plasma. Prospective trials and prospective hemovigilance studies are required to determine the rate of adverse events occurring after treatment with solvent/detergent-treated plasma and other types of therapeutic plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 24 publications
5
87
0
3
Order By: Relevance
“…In order to decrease the content of protein S there is an increased risk for thrombosis [37] or hyperfibrinolysis may be augmented due to a decreased content of α 2 -AP [38]. Approximately 30% of the fibrinogen is also affected and destroyed [39] during methylene blue pathogen inactivation, which results in reduced fibrin polymerization and again impairs the efficacy of FFP.…”
Section: Management Of Hepatic Coagulopathymentioning
confidence: 99%
“…In order to decrease the content of protein S there is an increased risk for thrombosis [37] or hyperfibrinolysis may be augmented due to a decreased content of α 2 -AP [38]. Approximately 30% of the fibrinogen is also affected and destroyed [39] during methylene blue pathogen inactivation, which results in reduced fibrin polymerization and again impairs the efficacy of FFP.…”
Section: Management Of Hepatic Coagulopathymentioning
confidence: 99%
“…The observed safety of Uniplas, with respect to fibrinolysis and thromboembolism, is in accordance with experience with Octaplas. 15 In Europe, a retrospective study has raised concerns about venous thromboembolism in patients with thrombotic thrombocytopenic purpura who had plasma exchange with Octaplas. 27 This could be attributed to the fact that protein S is reduced to the lower normal range in Octaplas and Uniplas.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that both products are SD-treated by similar methods, significant product differences, ascribed to production methods and type of plasma used, have been reported. 13,14,15 Such differences could explain the complications observed in the US. 15 In Europe, three prospective, randomized and three observational studies have demonstrated a similar clinical efficacy of SD-treated plasma and fresh-frozen single donor plasma in various clinical settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, S/D can't inactivate non-enveloped virus, such as hepatitis A virus (HAV) and parvovirus B19. Various studies [5][6][7] showed that treatment of S/D could reduce the activity of coagulation factors (CFs), inhibitors, immunoglobulins and other plasma proteins by about 5-20%. S/D treatment is safe and the final S/D reagents removal step ensures the final product is non toxic.…”
Section: Pi/pr By Solvent/detergent (S/d)mentioning
confidence: 99%